Hydrophilic low-temperature direct bonding of diamond and Si substrates under atmospheric conditions. (15th January 2020) - Matsumae, Takashi; Kurashima, Yuichi; Umezawa, Hitoshi; Takagi, Hideki
Abstract: A monocrystalline diamond substrate was directly bonded with a Si substrate by annealing at low temperatures under atmospheric conditions. These substrate surfaces were functionalized with hydroxyl groups and subsequently bonded by a dehydration reaction. When a diamond (111) substrate was treated with a H2 SO4 /H2 O2 mixture, it generated a direct bonding with an oxygen-plasma-activated Si substrate without significant loss in diamond crystallinity. The proposed bonding technique would contribute to the diamond device fabrication because the high-crystallinity diamond layer can be transferred by the commonly used cleaning process followed by low-temperature annealing under atmospheric conditions. Graphical abstract: Unlabelled Image